Portrayal of child abuse news stories in jaffna newspapers - Tharumarajah, K. (University of Jaffna, 2012)
This paper examines the role of the Jaffna’s newspaper in relation to child abuse and child protection and argues that the media have been essential to the task of placing the problem of child abuse in the minds of the public and on the political agenda. The media have played a major role in defining what is "normal" and what is "deviant" in society, thus contributing to definitions of what is, and what is not, considered to be child abuse. Talking about child abuse is a sensitive sub-ject for many because of varying beliefs. Some believe that all abuse should be reported while others believe cases of abuse should not be reported by the media at all. There are also laws at work regarding the media. Sometimes media reports revealed the abused of children being abused and neglected, but no names were revealed, and rightly so. It is essential of protection of child abuse victims. When a victim of child abuse dies due to the abuse they suffered, their name and age is often listed by the media. However, when a child is being abused and the horrific details are exposed, no names are listed, in order to protect the minor child. It is said that the privacy of children should be honored; however, all abuse should be reported. How can we expect our society to take abuse seriously if no abuse is reported For instance, if a child is being abused then the abuse should be reported while continuing to protect the privacy of the child. The more the media reports abuse, the more educated the public becomes. An example would be if the child protective agency confirms abuse then the media should report it. They must never reveal the name of the child. However, reporting that another case of abuse has occurred will help to educate the public. Media should have an active role in reporting abuse. The more awareness is raised, the more our society can attempt to prevent child abuse. But Media should follow some ethics to report child abuse news stories.
Keywords: Child abuse; Massmedia; Ethics